Indeks Komposit Pembangunan Infrastruktur Provinsi-Provinsi di Indonesia - Faradis, Royhan; Afifah, Uswatun Nurul (UI Scholars Hub, 2020)
Infrastructure development is absolutely necessary to improve Indonesia’s economic growth which carries the principles of pro-poor, pro growth, and pro-jobs. However, the conditions of each region are different so that these objectives are always accompanied by inequality in development outcomes. This study maps areas that experience inequality into a composite index using factor analysis. This composite index was built based on the development of methods by the OECD. The results showed that Indeks Pembangunan Infrastruktur (IPI) was a valid measure. Seven provinces are categorized as inadequate located in Kalimantan and eastern Indonesia. The seven provinces have infrastructure and health and economic dimensions below the national average.